The Long-term Efficacy and Safety of Fecal Microbiota Transplant for Recurrent, Severe, and Complicated Clostridium difficile Infection in 146 Elderly Individuals. Issue 5 (May 2016) - Agrawal, Manasi; Aroniadis, Olga C.; Brandt, Lawrence J.; Kelly, Colleen; Freeman, Sarah; Surawicz, Christina; Broussard, Elizabeth; Stollman, Neil; Giovanelli, Andrea; Smith, Becky; Yen, Eugene; Trivedi, Apurva; et al.
Abstract : Objectives: Clostridium difficile infection (CDI) in the elderly has a higher prevalence, greater morbidity and mortality, and lower response to conventional treatment than the general population. Fecal microbiota transplant (FMT) is highly effective therapy for CDI but has not been studied specifically in the elderly. This study aims to determine the long-term efficacy and safety of FMT for recurrent (RCDI), severe (SCDI), and complicated (CCDI) CDI in elderly patients. Methods: A multicenter, long-term follow-up study was performed with demographic, pre-FMT, and post-FMT data collected from elderly patients with RCDI, SCDI, and CCDI, through a 47-item questionnaire. Outcome measures included primary and secondary cure rates, early (<12 wk) and late (≥12 wk) recurrence rates, and adverse events (AEs), including post-FMT diagnoses. Results: Of 168 eligible patients, 146 patients met the inclusion criteria. Of these, 68.5% were women. The mean (range) age was 78.6 (65 to 97) years and the follow-up period was 12.3 (1 to 48) months. FMT was performed for RCDI in 89 (61%), SCDI in 45 (30.8%), and CCDI in 12 (8.2%) patients. The primary and secondary cure rates were 82.9% and 95.9%, respectively. Early and late recurrences occurred in 25 and 6 patients, respectively. AEs included CDI-negative diarrhea in 7 (4.8%) and constipation in 4 (2.7%) patients. Serious AEs, recorded in 6 patients, were hospital admissions for CDI-related diarrhea, one of which culminated in death. New diagnoses post-FMT included microscopic colitis (2), Sjogren syndrome (1), follicular lymphoma (1), contact dermatitis and idiopathic Bence-Jones proteinuria (1), and laryngeal carcinoma (1)—all, however, were associated with predisposing factors. Conclusions: FMT is a safe and effective treatment option for RCDI, SCDI, and CCDI in elderly patients.